Однонуклеотидный полиморфизм гена интерлейкина-6 (IL-6) у жителей Харькова, больных сахарным диабетом 2 типа - Козак, Н.А.; Почерняев, А.К.; Лыткин, Д.В.; Горшунская, М.Ю.; Почерняева, С.С. (Фактори експериментальної еволюції організмів, 2015)
Aims. To examine the association between SNP rs2069840 (174G / C) of interleukin-6 gene and type 2 diabetes in the population of Kharkov. Objects were venous blood samples of 60 patients with type 2 diabetes and 49 healthy persons (all residents of Kharkiv, Ukrainian and Russian). Methods. Genotyping by PCR-RFLP. Results. The distribution of genotypes for SNP rs2069840 corresponds to the Hardy-Weinberg equilibrium. Allele frequencies in the control group is 0.5; in the group of patients pC = 0.4, qG = 0.6. The weak non-signifi cant association between CC genotype and type 2 diabetes was marked. The odds ratio for genotype GG is 0.54. The sensitivity of the test is 15 %, specificity — 76 %. The positive predictive value is equal to 2 %, negative — 97 %, the accuracy of the test is 74 %, positive likelihood ratio result is 0.63, a negative — 1.6. Conclusions. The distribution of genotypes for SNP rs2069840 of interleukin-6 in the Kharkov population does not deviate from the Hardy-Weinberg equilibrium. According to the results of a pilot study was founded that the CC genotype increases the risk of type 2 diabetes in 1.2 times.